The influence of immune regulation mediated by intestinal microbiota on postmenopausal osteoporosis and intervention strategies - Wang, Lili; Chen, Shiqing; Cai, Xiaoyu; Zheng, Yongquan; Zheng, Caihong; Yao, Yao (Frontiers in Endocrinology, 2026)
Postmenopausal osteoporosis (PMO) is a common metabolic bone disease characterized by reduced bone mass and deteriorated bone microarchitecture, leading to an increased risk of fractures. In recent years, growing evidence has highlighted the role of gut microbiota and its immune-mediated regulation in the pathogenesis and progression of PMO. The gut microbiota modulates host immune responses, influencing the balance between bone resorption and bone formation. Estrogen deficiency after menopause disrupts gut microbiota composition, induces systemic inflammation, and promotes osteoclast activation, accelerating bone loss. Moreover, specific microbial communities and their metabolites, such as short-chain fatty acids (SCFAs), regulate bone metabolism by modulating immune cells, including T cells, B cells, and macrophages. Various microbiota-targeted interventions, such as probiotics, prebiotics, and fecal microbiota transplantation (FMT), have shown potential in improving bone health. However, several challenges remain, including individual variability in microbiota composition, the long-term effects of interventions, and their clinical applicability. Further investigations into the gut microbiota-mediated immune regulation of PMO may provide novel insights and therapeutic strategies for osteoporosis prevention and treatment.